2023
DOI: 10.1021/acsnano.2c10352
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralized MnO2 Nanoplatforms Mediated Delivery of Immune Checkpoint Inhibitors with STING Pathway Activation to Potentiate Cancer Radio-Immunotherapy

Abstract: Radiotherapy (RT), as one of the main methods in the clinical treatment of various malignant tumors, would induce systemic immunotherapeutic effects by triggering immunogenic cell death (ICD) of cancer cells. However, the antitumor immune responses produced by RT-induced ICD alone usually are not robust enough to eliminate distant tumors and thus ineffective against cancer metastases. Herein, a biomimetic mineralization method for facile synthesis of MnO 2 nanoparticles with high antiprogrammed death ligand 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Such activation of the cGAS-STING pathway induces the generation of type I interferons (IFNs) to improve antigen presentation by dendritic cells (DCs) for augmented antitumor T cell responses. With these merits, innovative nanoplatforms such as amorphous porous manganese phosphate nanoparticles (NPs), biomineralized manganese dioxide (MnO 2 ), Mn 2+ -coordinated micelles, and metal-phenolic networks , have been developed for successful cGAS-STING-associated combination immunotherapy. Although Mn-based nanosystems have emerged as potent weapons in tumor immunotherapy, because of their multiple functions in immune activation, TME remodeling, and MR imaging monitoring, there are rare reports to integrate all the advantages of Mn in one nanoplatform for enhanced cancer treatment, especially by the combination of natural enzyme-based catalysts, metal-based catalysts, and immune stimulating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Such activation of the cGAS-STING pathway induces the generation of type I interferons (IFNs) to improve antigen presentation by dendritic cells (DCs) for augmented antitumor T cell responses. With these merits, innovative nanoplatforms such as amorphous porous manganese phosphate nanoparticles (NPs), biomineralized manganese dioxide (MnO 2 ), Mn 2+ -coordinated micelles, and metal-phenolic networks , have been developed for successful cGAS-STING-associated combination immunotherapy. Although Mn-based nanosystems have emerged as potent weapons in tumor immunotherapy, because of their multiple functions in immune activation, TME remodeling, and MR imaging monitoring, there are rare reports to integrate all the advantages of Mn in one nanoplatform for enhanced cancer treatment, especially by the combination of natural enzyme-based catalysts, metal-based catalysts, and immune stimulating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that activation of innate immunity has emerged as a hopeful strategy to expedite cancer immunotherapy; , as a key component of innate immunity, the cyclic GMP–AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway also plays a crucial role in activating antitumor immune response and reshaping tumor microenvironment (TME). Briefly, the activation of the cGAS-STING pathway can promote the production of type I interferon (IFN) and the secretion of pro-inflammatory cytokines, thereby inducing innate immune response, increasing T lymphocyte infiltration, improving tumor immunosuppressive microenvironment, and is expected to enhance the efficacy of MWTT-ICB combined therapy. According to recent researches, Mn 2+ can comprehensively enhance the activation of cGAS , and initiate the cGAS-STING pathway to obtain synergistic antitumor efficacy. , Some Mn 2+ -based treatment strategies have made conspicuous progress in clinical trials. Thus, it is highly desirable to design a targeted and responsive delivery system that generates sufficient Mn 2+ to activate the cGAS-STING pathway in tumor cells, while achieving high concentration accumulation and penetration of immune agents.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia in tumor microenvironment (TME) is one of the most important factors that limit the effect of antitumor therapy. For instance, oxygen plays a pivotal role in stabilizing DNA damages; typically, hypoxia limits radiation-induced DNA damages and thus induces radiotherapy resistance. , Besides, hypoxia suppresses the photosensitizer (PS) to photosensitize oxygen (O 2 ) into reactive oxygen species (ROS), , which further impairs the efficacy of photodynamic therapy (PDT). Therefore, hypoxia relief is crucial for cancer treatment, and several methods have been performed to relieve hypoxia nowadays, including improving oxygen delivery, in situ oxygen generation, and inhibiting cellular respiration. Escherichia coli (E. coli), with tumor-targeting ability and catalytic property under TME, can effectively release catalase after entering the tumor cells.…”
Section: Introductionmentioning
confidence: 99%